Cardiovascular risk in myositis patients compared with the general population - Oreska, Sabina; Storkanova, Hana; Pekacova, Aneta; Kudlicka, Jaroslav; Tuka, Vladimir; Mikes, Ondrej; Krupickova, Zdislava; Satny, Martin; Chytilova, Eva; Kvasnicka, Jan; Spiritovic, Maja; Hermankova, Barbora; et al. (Rheumatology (Oxford, England), 2024)
OBJECTIVES: We aimed to evaluate cardiovascular (CV) risk in patients with idiopathic inflammatory myopathies (IIM) compared with healthy controls (HC) and to assess its association with disease-specific features. METHODS: Ninety IIM patients and 180 age-/sex-matched HC were included. Subjects with a history of CV disease (angina pectoris, myocardial infarction and cerebrovascular/peripheral arterial vascular events) were excluded. All participants were prospectively recruited and underwent examinations of carotid intima-media thickness (CIMT), pulse wave velocity (PWV), ankle-brachial index (ABI), and body composition. The risk of fatal CV events was evaluated by the Systematic COronary Risk Evaluation (SCORE) and its modifications. RESULTS: Compared with HC, IIM patients had a significantly higher prevalence of traditional CV risk factors, carotid artery disease (CARD), abnormal ABI and PWV. After propensity score matching (using traditional CV risk factors), the prevalence of CARD and pathological PWV remained significantly higher in IIM than HC. No significant difference in SCORE was observed. The most unfavourable CV risk profile was observed in patients with necrotizing myopathy, especially in statin-induced anti-HMGCR+ patients. The calculated CV risk scores by SCORE, SCORE2 and SCORE multiplied by the coefficient 1.5 (mSCORE) were reclassified according to CIMT and the presence of carotid plaques. SCORE was demonstrated to be most inaccurate in predicting CV risk in IIM. Age, disease activity, lipid profile, body composition parameters and blood pressure were the most significant predictors of CV risk in IIM patients. CONCLUSION: Significantly higher prevalence of traditional risk factors and subclinical atherosclerosis was observed in IIM patients compared with HC.
Keywords: myositis; analýza pulzové vlny; myozitida; inflammation; cardiovascular risk; Pulse Wave Analysis; Heart Disease Risk Factors; Cardiovascular Diseases; intimomediální šíře tepenné stěny; Myositis; nemoci arterie carotis; Carotid Intima-Media Thickness; Humans; kardiovaskulární nemoci; rizikové faktory; atherosclerosis; rizikové faktory kardiovaskulárních chorob; Risk Factors; Carotid Artery Diseases; lidé